Snapdoc: usos do snapchat na cobertura das eleições municipais de São Paulo pelo Uol - Stevani, Cleber (2018)
Snapchat is a social video network and its main features are the vertical format, perpetuated by the application due to the operational exclusivity in smartphones and handsets, and the ephemerality of the content, in what was a pioneer. The platform came out in 2011 with the purpose of making videos with simple and fun language. Emojis are very popular and fundamental to complement communication between users - mostly young people of named generation Y, or "millennials". With the growth of Snapchat in recent years, newspaper companies have invested in the application to bring information and engage that audience to their respective platforms, particularly in the United States. In Brazil, the UOL portal is the journalistic medium that produces the most content for Snapchat. Given this scenario, the present study make an analysis of the use of Snapchat in the coverage of the municipal elections of São Paulo in 2016 by UOL. The research maps and analyzes the uses the portal made of Snapchat on occasion and uses the data to support the production of a small documentary about Snapchat's potential for journalism in the digital age. After a bibliographical survey, interviews and content analysis we understand that Snapchat is an application that has been of little use by the Brazilian press and we have produced a nine-minute small video on the subject, in Snapchat format.